2014
DOI: 10.1242/dev.104760
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum of Fates: a new approach to the study of the developing zebrafish retina

Abstract: The ability to image cells live and in situ as they proliferate and differentiate has proved to be an invaluable asset to biologists investigating developmental processes. Here, we describe a Spectrum of Fates approach that allows the identification of all the major neuronal subtypes in the zebrafish retina simultaneously. Spectrum of Fates is based on the combinatorial expression of differently coloured fluorescent proteins driven by the promoters of transcription factors that are expressed in overlapping sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
61
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(68 citation statements)
references
References 46 publications
7
61
0
Order By: Relevance
“…Embryos were raised at temperatures ranging from 28.5 to 32 °C and staged in hours post-fertilization (hpf) according to Kimmel and collaborators (Kimmel et al, 1995). We used wild-type (Tab5), SoFa1 triple transgenic (atoh7:gap-RFP/ptf1a:cytGFP/crx:gap-CFP; Almeida et al, 2014) and the CRISPRgenerated mutant line NM_131753.1:g.30_39del (hereafter denoted as slit2-/-). All the manipulations were carried out following the approved local regulations (CEUA-Institut Pasteur de Montevideo, and CNEA).…”
Section: -Fish Breeding and Carementioning
confidence: 99%
“…Embryos were raised at temperatures ranging from 28.5 to 32 °C and staged in hours post-fertilization (hpf) according to Kimmel and collaborators (Kimmel et al, 1995). We used wild-type (Tab5), SoFa1 triple transgenic (atoh7:gap-RFP/ptf1a:cytGFP/crx:gap-CFP; Almeida et al, 2014) and the CRISPRgenerated mutant line NM_131753.1:g.30_39del (hereafter denoted as slit2-/-). All the manipulations were carried out following the approved local regulations (CEUA-Institut Pasteur de Montevideo, and CNEA).…”
Section: -Fish Breeding and Carementioning
confidence: 99%
“…Transgenic lines used line structures labeled reference Tg(bactin:GFP-DCX) all microtubules this study aPKC in all membranes this study Tg(bactin:ras-GFP) all membranes gift from C.P. Heisenberg lab Tg(ath5:gap-GFP) membranes of RGCs and photoreceptors (Zolessi et al, 2006) Tg(ath5:gap-RFP) membranes of RGCs and photoreceptors (Zolessi et al, 2006) Tg(crx:gap-CFP) membranes of photoreceptors and bipolar cells (Almeida et al, 2014) Tg(ptf1a:DsRed) amacrine and horizontal cells (Jusuf et al, 2012) Tg(ptf1a:Gal4-VP16, UAS:gap-YFP) membranes of amacrine and horizontal cells (Pisharath and Parsons, 2009) (Williams et al, 2010) Tg(SoFa2) all retinal cells (Almeida et al, 2014) Tg(vsx1:GFP) bipolar cells (Kimura et al, 2008) DNA constructs ath5:mKate2-aPKC-CAAX The coding sequence of mKate2-aPKC-CAAX was assembled by classical cloning in the pCS2+ backbone and used as a template for creating the mKate2-aPKC-CAAX middle entry clone by PCR using Phusion polymerase (NEB) with primers: F: 5′-ggggacaagtttgtacaaaaaagcaggctggATGGTGAGCGAGCTGATTAAGG-3′ R: 5′-ggggaccactttgtacaagaaagctgggtcTTAGGAGAGCACACACTTG-3′ The Ath5 promoter 5′ entry clone (Kwan et al, 2007) was combined with mKate2-aPKC-CAAX middle entry clone and pTol2+pA R4-R2 backbone (Villefranc et al, 2007).…”
Section: Supplemental Materials and Methodsmentioning
confidence: 99%
“…Heat shock was performed between 30 hpf and 32 hpf so that aPKC-CAAX was present when RGC emergence was at its peak. Live imaging revealed that in this condition RGCs indeed lost their basal process after apical division and for more than 6 hours did not lose their apical process To assess whether this impairment of RGC translocation had long-lasting effects on retinal lamination, we performed long-term imaging of Tg(hsp70:mKate2-aPKC-CAAX) fish crossed with the SoFa2 line (Almeida et al, 2014), which labels membranes of all retinal cells using a combination of three fluorescent proteins. Fish were imaged in the LSFM every 12 hours between 36 hpf and 84 hpf to follow retinal lamination ( Fig.…”
Section: Complete Arrest Of Rgc Translocation and Their Ectopic Maturmentioning
confidence: 99%
“…Further increasing this number requires spectral unmixing but at signicant cost in terms of photon budget and computation time. [15][16][17][18][19][20][21][22] Such constraints currently limit the discriminative power of emerging genetic engineering strategies, [23][24][25] which can already be implemented to label a larger number of biomolecules or cells in order to interrogate signaling pathways, 26 cycling states, 27 genotypes, 28,29 neuronal projections, 23,30,31 clones, [26][27][28][29][30][31][32][33] cell types, 34 or microbiomes. 35 Since uorescence should remain a much favored observable for imaging live cells, 36 the spectral dimension has to be complemented by another dimension for further discriminating uorophores (see Fig.…”
Section: Spectral Discrimination At Its Limitsmentioning
confidence: 99%